The Probe for Renal Organic Cation Secretion (4-Dimethylaminostyryl)-N-Methylpyridinium (ASP+)) Shows Amplified Fluorescence by Binding to Albumin and Is Accumulated In Vivo. (22nd March 2022) - Engbjerg, Jacob Schade; Costanzo, Vincenzo; Sardella, Donato; Bordoni, Luca; Jakobsen, Steen; D'Apolito, Luciano; Frøkiær, Jørgen; Trepiccione, Francesco; Capasso, Giovambattista; Frische, Sebastian
Abstract : Accumulation of uremic toxins may lead to the life-threatening condition "uremic syndrome" in patients with advanced chronic kidney disease (CKD) requiring renal replacement therapy. Clinical evaluation of proximal tubular secretion of organic cations (OC), of which some are uremic toxins, is desired, but difficult. The biomedical knowledge on OC secretion and cellular transport partly relies on studies using the fluorescent tracer 4-dimethylaminostyryl)- N -methylpyridinium (ASP+), which has been used in many studies of renal excretion mechanisms of organic ions and which could be a candidate as a PET tracer. This study is aimed at expanding the knowledge of the tracer characteristics of ASP+ by recording the distribution and intensity of ASP+ signals in vivo both by fluorescence and by positron emission tomography (PET) imaging and at investigating if the fluorescence signal of ASP+ is influenced by the presence of albumin. Two-photon in vivo microscopy of male Münich Wistar Frömter rats showed that a bolus injection of ASP+ conferred a fluorescence signal to the blood plasma lasting for about 30 minutes. In the renal proximal tubule, the bolus resulted in a complex pattern of fluorescence including a rapid and strong transient signal at the brush border, a very low signal in the luminal fluid, and a slow transient intracellular signal. PET imaging using 11 C-labelled ASP+ showed accumulation in the liver, heart, and kidney. Fluorescence emission spectra recorded in vitro of ASP+ alone and in the presence of albumin using both 1-photon excitation and two-photon excitation showed that albumin strongly enhance the emission from ASP+ and induce a shift of the emission maximum from 600 to 570 nm. Conclusion . The renal pattern of fluorescence observed from ASP+ in vivo is likely affected by the local concentration of albumin, and quantification of ASP+ fluorescent signals in vivo cannot be directly translated to ASP+ concentrations.